Wyrazy zapożyczone z języka polskiego w słowniku gwar smoleńskich Włodzimierza Dobrowolskiego - Wójtowicz, Marian (Studia Rossica Posnaniensia, 2019)
The analysis comprises a stock of 414 Polish loanwords selected from the dictionary of Smolensk dialects. In the article the following problems are discussed: the stock of loanwords, periods and the process of the borrowing. Most of the words were borrowed as a result of direct language contacts. Some of the words were borrowed through Belarussian. The majority of them were borrowed in the 17th, 19th and at the beginning of the 20th century.